Direct electrosynthesis for N-alkyl-C3-halo-indoles using alkyl halide as both alkylating and halogenating building blocks. Issue 10 (29th April 2019) - Sun, Linhao; Zhang, Xing; Wang, Chenguang; Teng, Huailong; Ma, Jimei; Li, Zilong; Chen, Hao; Jiang, Hong
Abstract : An electrochemically induced tandem reaction has been developed for selective N1-alkylation and C3-halogenation of indoles. Abstract : An electrochemically induced tandem reaction has been developed for selective N1-alkylation and C3-halogenation of indoles. This electrochemical difunctionalization strategy circumvents conventional multi-step procedures and efficiently generates synthetically important N -alkyl-3-halo-indoles under more environmentally benign conditions. This reaction can proceed in a simple undivided cell, without the use of any oxidant, base or transition-metal. The excellent atom-economy of this method is highlighted by fully using alkyl halide as both alkylating and halogenating building blocks without atom waste.